Peran Dewan Perwakilan Rakyat Kabupaten Aceh Singkil dalam Rencana Kebijakan Pembangunan Daerah Berdasarkan Peraturan Menteri dalam Negeri Nomor 86 Tahun 2017 - Julkarnaen Julkarnaen; Dani Sintara (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
The Regional People's Representative Council's Pokir is the result of absorbing community aspirations conveyed by members of the Regional People's Representative Council in official and informal forums. This Pokir aims to ensure that regional development policies reflect the needs and desires of the local community.To determine the role of the Aceh Singkil Regency People's Representative Council in formulating regional development policy plans through the Main Thoughts (Pokir) of the Regency People's Representative Council In legal research, there are two types of research, namely normative (doctrinal) research and empirical research. The type of research used in compiling this thesis is a combination of normative (doctrinal) research and empirical research. Data collection methods are techniques or methods that can be used by researchers to collect data. Techniques in designating an abstract word that is not manifested in objects, but can only be seen in its use through: questionnaires, interviews, observations, exams (tests), documentation, and others. The data analysis technique used in this legal research uses qualitative analysis methods Based on the results of the study, the Regency People's Representative Council also plays a role in determining the regional budget that will fund various development programs. In this process, the District People's Representative Council must ensure that the budget prepared reflects the development priorities that have been set based on community aspirations. Thus, the District People's Representative Council not only acts as a political representative, but also as a supervisor of budget use to ensure transparency and accountability in regional financial management. The results of the discussion regarding the role of the Aceh Singkil District People's Representative Council (DPRK) in preparing the main ideas (Pokir) show that the DPRK has a crucial role in regional development policy planning. In accordance with the Regulation of the Minister of Home Affairs Number 86 of 2017, the DPRK functions as a liaison between the community and the regional government by preparing Pokir that reflects the aspirations and needs of the community.So it can be concluded that according to the regulations, the District People's Representative Council is tasked with preparing the Main Ideas (Pokir) which are the results of absorbing community aspirations. This Pokir is then submitted to the regional government to be used as a basis for preparing development planning documents, such as the Regional Medium-Term Development Plan (RPJMD) and the Regional Government Work Plan (RKPD).